Avaliação, por meio da metodologia Fuzzy, da confiabilidade de sistemas de acionamento submetidos a fatores de estresse ambientais - Frederico Augusto Lopes Souza (2015)
This work presents contributions to the study of the reliability of drive systems constituted by induction motors driven by frequency converters as well as considering the influence from environmental aspects on the failure rates of a system components, therefore characterizing the physical-chemical effects which occur when electronic components are exposed to harsh environment such as vibration, dust, humidity, high temperatures, among others, and how those effects can reduce the component useful life. Herewith it is also presented a compilation of the results of a wide and deep research on the different reliability prediction standards, as well as on of environment classification standards, by means of a critical and comparative analysis of different techniques, methodologies and applications of each standard under study. A method for correcting the failure rates of electronic components, due to environmental aspects influence, is also presented in this work. Aiming at that, a Fuzzy Rule Based System is used, therefore making it possible for a reliability analysis by means of a more coherent and precise way. At last, an example is presented of a low-voltage drive system whose main merit figures of reliability are determined and discussed when that system is under harsh environment - mining, maritime (oil extraction), and steel processing